1977
DOI: 10.1210/jcem-44-5-963
|View full text |Cite
|
Sign up to set email alerts
|

hCG Binding and Stimulation of Testosterone Biosynthesis in the Human Fetal Testis

Abstract: The role of hCG in the regulation of testicular steroid production in human fetuses from 14 to 20 weeks gestational age was studied. Saturable binding of 125I-hCG to testicular homogenates was demonstrated, and physiologic concentrations of hCG were able to stimulate testosterone formation in testicular minces without the addition of exogenous precursors. In five fetses of 16-20 weeks gestational age, the capacity to bind hCG varied from 25.6 to 42.2 pg/mg wet tissue. The association constant of binding was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(54 citation statements)
references
References 15 publications
3
49
0
2
Order By: Relevance
“…Although the mechanism of neoplastic elaboration of these proteins is unknown, some workers have postulated that this represents a reversion to fetal gene expression (2). In studying the physiologic role of hCG in the human fetuis, we found that the human fetal testes (3) and adrenal (4) responded to hCG administration with increased steroidogenesis in vitro. To determine the relative hCG content in the fetus, the hCG concentration in homogenates of various fetal tissues was measured using an hCG 1-subunit (,B-hCG) radioimmunoassay Received for publication 23 10% in NET buffer) was added to the suiperinatte.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the mechanism of neoplastic elaboration of these proteins is unknown, some workers have postulated that this represents a reversion to fetal gene expression (2). In studying the physiologic role of hCG in the human fetuis, we found that the human fetal testes (3) and adrenal (4) responded to hCG administration with increased steroidogenesis in vitro. To determine the relative hCG content in the fetus, the hCG concentration in homogenates of various fetal tissues was measured using an hCG 1-subunit (,B-hCG) radioimmunoassay Received for publication 23 10% in NET buffer) was added to the suiperinatte.…”
Section: Introductionmentioning
confidence: 71%
“…The role of hCG in the regulation of human fetal testes is of extreme interest in light of the hCGstimulated testosterone production and the highaffinity binding of the hormone found in this tissue (3). Unfortunately the minute size of the fetal gonad at this stage of gestation has precluded tissue explant study to date.3 The origin and role of the high concentration of hCG in ovary and thymus also remain obscure and await further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The production of CG is confined to human, primate and equine placentas, whereas only pituitary LH is produced in rodents, including the mouse. hCG is essential for the maintenance of human pregnancy by stimulating progesterone production of corpus luteum gravidarum, and it also stimulates testosterone production of fetal Leydig cells (Huhtaniemi et al, 1977;Huhtaniemi and Pelliniemi, 1992;Huhtaniemi, 1994). In contrast to humans, the mouse genome does not contain a gene encoding chorionic gonadotroin.…”
Section: Introductionmentioning
confidence: 99%
“…Male phenotype is controlled by two testicular hormones, the anti-Mullerian hormone (AMH) secreted by fetal Sertoli cells which induces regression of the Mullerian ducts (Josso et al, 1993(Josso et al, , 1998, and testosterone produced by fetal Leydig cells which induces differentiation of the Wolffian ducts into male reproductive organs (Winter et al, 1977). It is known that secretion of the human chorionic gonadotrophin (hCG) achieves a maximum peak around 80 days of gestation (Kaplan et al, 1976;Huhtaniemi et al, 1977;Mulchaney et al, 1987), and testosterone production was starts around 50 days of gestation and declines slowly after 100 days (Huhtaniemi, 1989). However, little information about the histological maturation of the testicular cord around 80 days of gestation is available.…”
Section: Introductionmentioning
confidence: 99%